In Situ Solar Panel Output Power Measurement Related to Climate Parameters using Digital Recording - Mardiyono Mardiyono; Endro Wasito; Sugeng Ariyono (IAES Indonesia Section, 2015)
Solar energy in tropical area is one of potential renewable energy due to the sun always shines along of a year involving in dry and rainy season. The power output of solar panel is depended on climate parameters including solar radiation, humidity, cloud, rain, and dust decomposition. This paper explores the climate parameters that potentially affect the power output of solar panel and estimate the solar energy in such region based on its climate parameters. To measure the climate and electric data, this work develops in house digital climate and electrical data recording that saves the data of humidity, wind speed, temperature, solar irradiance, current, and voltage sensors. The data are analyzed by equation of correlation between climate parameters, power output and solar panel temperature. The protoype of digital recording is tested at Politeknik Negeri Semarang located on latitude -7.054044 and longitude 110.434695 during dry season. Based on the correlation analysis of several climate parameters to solar panel output power, the correlation value of the humidity is -0.85, ambient temperature=0.87, solar irradiance=0.98, wind speed= -0.34 and cell temperature=0.83. This work can be used to estimate the potency of solar panel output power in specific location using climate data.